Quantitative biometric cutoffs for the choice of the intraocular lens power calculation formula for a recently introduced nondiffractive extended depth-of-focus intraocular lens. Issue 5 (September 2022) - Arrigo, Alessandro; Gambaro, Gianpiera; Fasce, Francesco; Aragona, Emanuela; Figini, Innocente; Bandello, Francesco
Purpose: This study aimed to analyze biometry values cutoffs for the choice of the best intraocular lens power calculation formula for AcrySof IQ Vivity intraocular lens. Methods: The study was designed as interventional case series with 3 months of follow-up. Intraocular lens power calculation formulas included Barrett Universal II and SRK/T. The first was adopted for the intraocular lens power choice. The quantitative analysis focused on the identification of specific biometric cutoffs considering axial length, anterior chamber depth, and corneal powers. We included only the dominant eye in the statistical analysis. Results: One hundred and eight eyes of 54 patients (23 males; mean age 62 ± 5 years) with no ocular diseases were included. Best-corrected visual acuity improved from 0.3 ± 0.2 to 0.0 ± 0.0 logMAR. All the eyes reached spectacles-free far and intermediate visions; a spherical addition of + 1.0D was necessary to adjust near vision. We identified significant quantitative cutoffs based on axial length and anterior chamber depth. Barrett Universal II resulted the best formula for eyes disclosing an axial length >25 mm, whereas SRK/T turned out to be the best choice for the eyes characterized by an anterior chamber depth <2.8 mm. Our analysis disclosed an overall sensitivity of 0.8 and a specificity of 0.7 ( p < 0.01). Conclusions: Axial length and anterior chamber depth influence the choice of Barrett Universal II and SRK/T formulas. Quantitative biometric cutoffs may be useful to discriminate the best formula to be adopted.